KERJASAMA LUAR NEGERI PEMERINTAH DAERAH DALAM MENDUKUNG PENGUATAN KEAMANAN MANUSIA (Studi Kasus Kerjasama Luar Negeri Pemprov D.I. Yogyakarta) - Fadhlan Hakiem; Ida Susilowati (UNIDA Gontor, 2020)
Decentralization provides significant authority for Local Government, either District / City or Provincial governments. This regulation gives Local Government authority to conduct international cooperation. This research aims at analyzing how the international cooperation of Local Government can strengthen human security in Indonesia. International cooperation and the role of local government can contribute to reinforcing human security. This contribution is expected to be able to describe the in-depth investigation of international cooperation carried out by the Local Government of Yogyakarta Province. Yogyakarta Province is one of the local governments performing a variety of international cooperations with various parties including government, private institutions, and non-governmental organizations. The research can be categorized as qualitative research done through a case study. The data will be collected through interviews and literature studies. The results of this research show that international cooperation undertaken by local governments indicates a significant role to strengthen human security, especially the protection for economic security.